Lumbosacral Edema as an Unusual Presentation of Henoch-Schönlein purpura: A Case Report and Literature Review - Yeom, Jung Sook; Seo, Ji-Hyun; Youn, Hee-Shang (Journal of Nepal Paediatric Society, 2022)
Henoch- Schönlein purpura (HSP) is the most common vasculitis of childhood. Subcutaneous edema in the extremities is a common finding of HSP, whereas lumbosacral edema is a rare presentation. We report a case of HSP in a six year old boy who visited the emergency department for acute - onset back pain with gait problems. An extensive radiologic workup was performed, but the patient was finally diagnosed with HSP based on knee and ankle edema with a few purpura. We described the clinical, imaging findings, and treatment of the current case and review the literature regarding this rare presentation of HSP.